CO2 regeneration energy requirement of carbon capture process with an enhanced waste heat recovery from stripped gas by advanced transport membrane condenser. (1st October 2022) - Tu, Te; Yang, Xing; Cui, Qiufang; Shang, Yu; Yan, Shuiping
Graphical abstract: Highlights: A CO2 regeneration test rig with a good stability and reliability was built. Transport membrane condenser (TMC)-based rich-split (RS) process was explored. Reboiler duty saving up to 21.7% was achieved for TMC-based RS process. TMC-based RS process had a high tolerance to the swing of regeneration conditions. TMC-based RS process had a low total cooling duty of cooling water. Abstract: This study proposed to build an energy efficient and reliable CO2 regeneration system, via the integration of an advanced transport membrane condenser (TMC) and principle of rich solvent-split (RS), namely the TMC-based RS system. With the monoethanolamine (MEA) solvent and a TMC module housed commercial 19-channel hydrophilic ceramic membranes, the operational stability and energy requirement of the proposed system were evaluated. With a relatively low error (i.e., ± 5%) of the overall mass balance, the proposed system exhibited excellent reliability in operation. Compared to the traditional CO2 regeneration process without the RS modification, the conventional system with only the RS modification showed 4.8% saving in the reboiler duty (kWh/kg-CO2 ) at the split fraction of 10%; while the TMC-based RS process showed up to 21.7% saving in the reboiler duty with 0.2 m 2 membrane area at the split fraction of 30%. The energy saving corresponded to a decrease from 5.2 MJ/kg-CO2 to 3.9 MJ/kg-CO2 in terms of the calculated CO2 regeneration heat requirement. The sensitivity analysis showed that the TMC-based RS system was less susceptible to variations in operation conditions, demonstrating a low and relatively stable reboiler duty. An additional benefit of the proposed system was the reduced consumption of cooling water.